Experiments on grain size segregation in bedload transport on a steep slope. (February 2020) - Frey, P.; Lafaye de Micheaux, H.; Bel, C.; Maurin, R.; Rorsman, K.; Martin, T.; Ducottet, C.
Highlights: Segregation results in the progressive establishment of a quasi-continuous region of small particles reaching a steady-state penetration depth. Image processed concentration-depth profiles and isolines show a logarithmic time decrease. The segregation dynamics is demonstrated to be dependent on the particle streamwise shear rate. Abstract: Sediment transport in mountain and gravel-bed-rivers is characterized by bedload transport of a wide range of grain sizes. When the bed is moving, dynamic void openings permit downward infiltration of the smaller particles. This process, termed here 'kinetic sieving', has been studied in industrial contexts, but more rarely in fluvial sediment transport. We present an experimental study of two-size mixtures of coarse spherical glass beads entrained by turbulent and supercritical steady water flows down a steep channel with a mobile bed. The particle diameters were 4 mm and 6 mm, and the channel inclination 10%. The spatial and temporal evolution of the segregating smaller 4 mm diameter particles was studied through the introduction of the smaller particles at a low constant rate into the large particle bedload flow at transport equilibrium. Particle flows were filmed from the side by a high-speed camera. Using original particle tracking algorithms, the position and velocity of both small and large particles were determined. Results include the time evolution of the layer of segregating smaller beads, assessment of segregation velocity and particle depth profiles. Segregation resulted in the progressive establishment of a quasi-continuous region of small particles reaching a steady-state penetration depth. The segregation dynamics showed a logarithmic time decreasing trend. This evolution was demonstrated to be dependent on the particle streamwise shear rate which decays downwards exponentially. This result is comparable to theories initially developed for dry granular flows.